Optimization of Online SKCK Services by Satintelkam in Realizing Prime Service in Kediri Police (Advances in Police Science Research Journal, 2024)
The aim of this research is to find out how the online SKCK service is implemented by Satintelkam at Kediri Police and the factors that influence online SKCK services by Satintelkam at Kediri Police. This research uses the optimization concept, the online SKCK concept, and the excellent service concept. Meanwhile, for theory, management theory, SWOT analysis theory, cooperation theory, and HR theory are used as analytical tools. The approach taken in this research is a qualitative approach and the type of research is descriptive research. The research results show that the implementation of online SKCK services by Satintelkam at the Kediri Police is considered less than optimal because there is a very large comparison between the very large number of manual SKCK applicants and the very few online SKCK applicants. This happened because of findings regarding factors that influence service implementation. Therefore, the advice given by the author here is to overcome obstacles in terms of organizational resources and improve the implementation of socialization to the community so that the public knows and can use the online SKCK service at the Kediri Police.
Keywords: optimalisasi; SKCK online; Pelayanan Prima